DEVELOPMENT OF OFFICIAL TRAVEL WARRANT INFORMATION SYSTEM (CASE STUDY: BATUCEPER SUB-DISTRICT) - Yuwan Jumaryadi; Achmad Fathoni; Tedjo Nugroho (STMIK Pringsewu Lampung, 2020)
The development of Information Technology is currently felt in various fields, especially those related to computers. Technological developments also made several new innovations in the current era of globalization. Along with the development of technology, computers that were previously data processing tools systems have increase the capabilities. The usage of computers can increase efficiency and effectiveness in some jobs, so it is not surprising that many organizations or companies use official travel warrant. At Batuceper sub-district, in its office activities, official travel warrant is required when the employee will travel to a certain place. The existing system still using Word or spreadsheet application where the employee should edit the file where the employee want to travel and then input the file to Microsoft Excel, and it requires a lot of time. By making Information Systems of Official Travel warrant can facilitate users in making travel warrant, official travel receipts, official travel reports, recapitulation of official travel expenses, and better management of official travel.